Augmentation of GPS for Hydrographic Applications Under Signal Masking - Ryan, S.; Stephen, J.; Keong, J. H.; Lachapelle, G.; Hare, R. (The International Hydrographic Review, 2018)
In critical coastal water areas where signal masking due to high topographic features is severe, GPS is known to be deficient in either one or both of two characteristics, namely availability and reliability, the latter being associated with the notion of quality assurance. Augmentation of GPS with either GLONASS and/or geostationary satellites, in addition to the use of height and clock constraints is becoming a viable alternative, the more so as cost effective GPS/GLONASS receivers become available. The question as to what degree this combined approach can resolve the above limitations is analyzed herein by first conducting a series of simulations and, second, by validating these simulations with actual marine tests. The simulations use worst-case anisotropic mask angles encountered for specific locations along Canada’s Pacific Coast. Availability is evaluated through dilution of precision (DOP), figures of merit, and reliability by internal and external reliability measures. The GPS/GLONASS/geostationary satellites analysis includes simulations with height and clock constraints to determine the impact of these constraints on availability and reliability. Each set of results are compared to GPS to assess the incremental benefits of each type of augmentation. The simulations are validated with actual DGPS/DGLONASS measurements collected on a survey launch off Sidney, B.C., Canada.